Dietary compared with blood concentrations of carotenoids and breast cancer risk: a systematic review and meta-analysis of prospective studies - Aune, Dagfinn; Chan, Doris SM; Vieira, Ana Rita; Navarro Rosenblatt, Deborah A; Vieira, Rui; Greenwood, Darren C; Norat, Teresa (The American journal of clinical nutrition, 2012)
Measurement errors in the dietary assessment of fruit and vegetable intake may attenuate associations with breast cancer risk and might explain the weak associations observed in epidemiologic studies. Carotenoid concentrations in blood are biomarkers of fruit and vegetable intake; however, no systematic assessment has compared dietary intake with blood concentrations of carotenoids and breast cancer risk. We conducted a systematic review and meta-analysis of prospective studies of dietary intake and blood concentrations of carotenoids and breast cancer risk. We searched PubMed and several other databases for relevant studies up to 31 August 2011. Random-effects models were used to estimate summary estimates. Of the 6 dietary carotenoids assessed, only intake of β-carotene was significantly associated with a reduced breast cancer risk (summary RR: 0.95; 95% CI: 0.91, 0.99; I(2): 0%) per 5000 μg/d (n = 10). In contrast, the summary RR for blood concentrations of carotenoids was 0.78 (95% CI: 0.61, 0.99; I(2): 53%) per 100 μg total carotenoids/dL (n = 7), 0.74 (95% CI: 0.57, 0.97; I(2): 43%) per 50 μg β-carotene/dL (n = 13), 0.82 (95% CI: 0.73, 0.92, I(2): 3%) per 10 μg α-carotene/dL (n = 12), and 0.68 (95% CI: 0.52, 0.89; I(2): 0%) per 25 μg lutein/dL (n = 6). Blood concentrations of carotenoids are more strongly associated with reduced breast cancer risk than are carotenoids assessed by dietary questionnaires. Our results suggest that the use of certain biomarkers may clarify inconsistent and weak results between dietary intake and breast cancer risk.